Epidemiology, ecology and human perceptions of snakebites in a savanna community of northern Ghana. - Yahaya Musah; Evans P K Ameade; Daniel K Attuquayefio; Lars H Holbech (Public Library of Science (PLoS), 2019)
Background Worldwide, snakebite envenomations total ~2.7 million reported cases annually with ~100,000 fatalities. Since 2009, snakebite envenomation has intermittently been classified as a very important 'neglected tropical disease' by the World Health Organisation. Despite this emerging awareness, limited efforts have been geared towards addressing the serious public health implications of snakebites, particularly in sub-Saharan Africa, where baseline epidemiological and ecological data remain incomplete. Due to poverty as well as limited infrastructure and public health facilities, people in rural Africa, including Ghana, often have no other choice than to seek treatment from traditional medical practitioners (TMPs). The African 'snakebite crisis' is highlighted here using regionally representative complementary data from a community-based epidemiological and ecological study in the savanna zone of northern Ghana. Methodology and findings Our baseline study involved two data collection methods in the Savelugu-Nanton District (in 2019 the district was separated into Savelugu and Nanton districts) in northern Ghana, comprising a cross-sectional study of 1,000 residents and 24 TMPs between December 2008 and May 2009. Semi-structured interviews, as well as collection of retrospective snakebite and concurrent rainfall records from the Savelugu-Nanton District Hospital and Ghana Meteorological Authority respectively over 10-years (1999-2008) were used in the study. Variables tested included demography, human activity patterns, seasonality, snake ecology and clinical reports. Complementary data showed higher snakebite prevalence during the rainy season, and a hump-shaped correlation between rainfall intensity and snakebite incidences. Almost 6% of respondents had experienced a personal snakebite, whereas ~60% of respondents had witnessed a total of 799 snakebite cases. Out of a total of 857 reported snakebite cases, 24 (~2.8%) died. The highest snakebite prevalence was recorded for males in the age group 15-44 years during farming activities, with most bites occurring in the leg/foot region. The highest snakebite rate was within farmlands, most severe bites frequently caused by the Carpet viper (Echis ocellatus). Conclusion The relatively high community-based prevalence of ~6%, and case fatality ratio of ~3%, indicate that snakebites represent an important public health risk in northern Ghana. Based on the high number of respondents and long recording period, we believe these data truly reflect the general situation in the rural northern savanna zone of Ghana and West Africa at large. We recommend increased efforts from both local and international health authorities to address the current snakebite health crisis generally compromising livelihoods and productivity of rural farming communities in West Africa.